Learners’ Satisfaction With the Website Performance of an Open and Distance Learning Institution: A Case Study - Datt, Gopal; Singh, Gagan (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2021)
This paper explores learners’ awareness of and satisfaction with the e-services that an open university provides its learners through its Website. The paper further highlights the influence of age, gender, and education levels on learners’ awareness and satisfaction levels. A case-study approach was adopted and an online survey was used to collect data from learners in various programs of study at Uttarakhand Open University, India. The questionnaire measured the awareness levels of learners regarding 15 frequently used e-services and their satisfaction levels with the 12 most frequently used e-services that the university offers. Results show that gender, age, and education level have a significant influence on the awareness and satisfaction level of the participants. When maturity level and education level of the participants increased, they are more aware of the e-services provided by the University. In some cases, up to 58% of users were unaware of the university’s e-services, and a large number of respondents were either dissatisfied with or undecided regarding the university’s e-services. Results indicate that infrastructure is required for learners’ optimal use of information and communication technology and the e-services that the university offers, including the provision of Internet connectivity at all of the university’s learning support centers.